Growth response of wheat and associated weeds to plant antagonistic rhizobacteria and fungi - Mustafa, Adnan; Naveed, Muhammad; Abbas, Tanveer; Saeed, Qudsia; Hussain, Azhar; Ashraf, Muhammad Nadeem; Minggang, Xu (Italian Journal of Agronomy, 2019)
Wheat is the staple cereal crop of Pakistan but its growth is rigorously affected by associated weeds. Present study evaluated the synergistic effect of plant antagonistic rhizobacteria and fungi on growth, yield and suppression of wheat-associated weeds. Wheat associated weeds Phalaris minor and Avena fatua were grown in pots containing wheat as well. Pseudomonas aeruginosa strain PAO1 and Trichoderma harzianum T-MN6 were used as amendments to check their effect on two major weeds of wheat. The combined application of PAO1 and T-MN6 reduced the shoot length of Phalaris minor up to 30% and Avena fatua 40%, root length 22% and 28%, fresh biomass 29% and 31% respectively over their sole application. Similarly, inoculation of PAO1 and T-MN6 alone and in combination considerably enhanced growth, yield and physiological parameters of wheat. It was inferred from this study that the synergistic application of PGPR and fungi is a promising option to suppress major weeds of wheat and to enhance growth and yield of wheat.